Successfully Managed Case Of Celphos Poisoning: A Case Report and Review - Pangeni, R; KC, R K (Journal of Nepal Health Research Council, 2015)
Aluminium phosphide poisoning is one of the major causes of suicidal deaths in developing countries like Nepal. It is one of the common fumigant available and is within easy access. It is primarily used for crop protection. However, it is one of the misused chemicals to commit suicide. In this case, the patient had hyperglycaemia, atrial fibrillation, severe metabolic acidosis, and shock and yet survived. The key to her survival was aggressive supportive management. Therefore, knowing all the prognostic factors along with aggressive management can be life saving in conditions when no antidotes are available.Â Keywords: aluminium phosphide; fetal poisoning; fumigant; suicide.